Some Subclasses of Multivalent Analytic Functions Involving A Certain Differential Operator - C.Selvaraj, M.Elumalai (Asian Journal of Current Engineering and Maths, 2017)
In this paper using differential operator, we introduce a certain subclass of multivalent analytic functions on the open unit disk. Such conditions are subordination and superordination to investigate some inclusion, convolution and inequality properties, distortion theorems and also sufficient conditions for multivalent starlikeness are discussed. Â  Keywords: Multivalent function, starlike function, subordination, superordination, differential operator. Â  AMS Subject Classification: 30C45